Stabilitas dan Ketergantungan: Dinamika Pengelolaan RKAS di SMP Katolik Angelus Custos II - Zahra, Rona Angelica; Ramadhani, Anindya Larasati; Nurcahya, Nafisha Khaylani Ika; Widiyanah, Ima (ARZUSIN, 2026)
Although the management of the School Activity and Budget Plan (RKAS) has received attention in various previous studies, research specifically discussing the dynamics of RKAS management in private schools with high dependence on student funds, suboptimal stakeholder involvement, and limited alternative funding sources remains limited. This study aims to analyze RKAS management, identify its strengths and weaknesses, and formulate recommendations for more transparent, participatory, and sustainable school financial management. This study used a qualitative approach with a descriptive design. The research informant was the school treasurer, who was selected through purposive sampling. Data were collected through interviews, observation, and documentation studies, and were then analyzed using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The results showed that RKAS management had been carried out systematically through the stages of budget planning, implementation, supervision, and evaluation. The research findings also showed transparency, accountability, clear task distribution, and the implementation of internal and external audits. However, the school still faced challenges in the form of dependence on student funds, suboptimal stakeholder involvement, and limited alternative funding sources. These findings contribute to the development of studies on educational financial management and expand understanding of RKAS management in private schools. The conclusion of this study affirms that transparency, stakeholder participation, funding diversification, and collaborative leadership are important factors in maintaining the sustainability of RKAS management. The implications of this study include theoretical contributions to the development of literature on educational financial management and practical implications for schools in strengthening more effective, transparent, and sustainable RKAS management.